Factors influencing visitor travel to festivals: challenges in encouraging sustainable travel. Issue 5 (4th May 2019) - Collins, Andrea; Potoglou, Dimitris
Abstract: This paper examines how visitor travel-mode choices to festivals are formed and how sustainable travel could be encouraged. The empirical analysis focuses on Hay Festival of Literature and Arts using semi-structured interviews with visitors. Themes and topics explored through the interviews were informed by theories of travel behaviour. Findings highlight a range of external and internal factors influencing visitor travel-mode choices, which are closely interrelated. External factors reflect environmental elements related to the location and type of overnight accommodation, festival location, travel time and quality of public transport services. Internal factors include autonomy in travelling different routes and times, travelling with young children, cost of travel and physical-health and mobility issues. An additional internal factor was routine use of the car and extension of this behaviour when travelling to the festival. Based on the consolidation of the empirical findings, this paper also proposes a new theoretical framework for capturing a more comprehensive understanding of event related travel decisions. To encourage further sustainable travel, festival organisers and policy makers should not only focus exclusively on travel time and cost but consider a wider array of factors that are unique to festivals and their geographic locations.